Sexual Dimorphism of Femur and its Clinical Significance - Kumari, Ranzeetha. D. K. V. Pavana (Academia Anatomica International, 2019)
Introduction: Assessment of human sex from skeletal remains plays a key role in anthropological and medico legal studies. Hence this study was taken to assess the sex form an isolated bone i.e. femur, with as far as possible minimal parameters to ascertain the sex. Subjects and Methods: A study was conducted with 100 non pathological femora. (50male, 50 females ) in different age groups of known sex. The present study was to determine the sex by using 5 parameters i.e Maximum length, Head vertical diameter, Transverse head diameter, Proximal breadth, Distal breadth of the femur has been taken because it gives some useful data in medico legal cases, When only the remains of femur bone were left in deceased individuals. The measurements of femur bone were taken with the help of osteometric board and Vernier calliper. Results: The readings were noticed. The readings were tabulated and subjected to statistical analysis. It was noticed that all the studied parameters were greater in males than in females. Conclusion: The present study on the determination of sex of femora will be more reliable basis for the sex determination because it shows the values in this geographical region. This is believed to be more useful in the investigative procedures in the Forensic Medicine and also in the field of orthopaedics.